Influence of Homogeneous Weak Electric Field on the Chemical Potential and Heat Capacity of Charged Fermion System (Journal of Atomic and Molecular Sciences, 2018)
In light of the semiclassical (Thomas-Fermi) approximation method, the thermodynamic properties of the charged fermion system in homogeneous weak electric field are studied. After deriving the relationship of chemical potential and heat capacity of charged fermion system changed with the external electric field, then the analytic formula of the chemical potential and heat capacity of charged fermion system in the high and low temperature approximation condition is desired. Moreover, the influence of the homogeneous weak electric field on the chemical potential and heat capacity are analyzed.
Keywords: charged fermion; chemical potential; heat capacity; homogeneous weak electric field.